Adaptation of the Triple Helix model in ukrainian IT clusters: potential, barriers, and prospects - Lypovetskyi, B.; Guryanova, L. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The article provides a comprehensive analysis of the possibilities for adapting the Triple Helix model to the functioning of Ukrainian IT clusters. It is noted that Ukraine’s IT sector demonstrates high resilience during periods of socio-economic and security challenges, ensuring foreign currency earnings, employment of highly qualified professionals, and flexibility of business processes. At the same time, the sector faces several barriers: insufficient cooperation between universities and business, and weak state involvement in shaping cluster policy. Key opportunities for IT cluster development, barriers, and prospects in the context of creating innovative ecosystems are identified. Based on the Triple Helix concept, the article examines the specifics of Ukrainian IT clusters as platforms for interaction between business, universities, and public authorities. It is found that clusters in Ukraine differ significantly in structure and institutional maturity: some associations include hundreds of companies and maintain active educational partnerships, while others operate locally and are oriented mainly toward the business community. The analysis reveals the dominance of the business sector in the Triple Helix interaction model, moderate university involvement in talent development, and weak, fragmented participation of the state, which limits the consistency of innovation policy and access to government support instruments. This constrains the scalability of cluster initiatives and their impact on national innovation policy. At the same time, clusters actively compensate for these gaps through international cooperation and participation in European projects, which facilitates the transfer of best practices and access to resources, partially offsetting weak state support. Based on the findings, practical recommendations for adapting the Triple Helix model are proposed: establishing a coordinating body for cluster development and financial support mechanisms; strengthening the integration of clusters into the modernization of educational programs, internships, and professional development; developing institutional intermediaries and incentives for involving civil society; integrating cluster structures of various types to ensure eco-industrial modernization of key and adjacent regions.